Penggunaan Media Sosial sebagai Upaya Pembangunan SDM di Indonesia - Abdul Aziz (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
Disruptive technology is an event that helps many people also bothering or harming some people with the help of technology. With the help of the digital observation method, we found a way to help people affected by the disruption, namely by using social media to spread useful information and knowledge. With these efforts, it is hoped that the community can take advantage of and enjoy the efforts that we provide